Being Positive is Not Everything – Experimental and Computational Studies on the Selectivity of a Self‐Assembled, Multiple Redox‐State Receptor that Binds Anions with up to Picomolar Affinities. Issue 5 (13th December 2021) - Zubi, Ahmed; Alnafisah, Hawazin A.; Turega, Simon; Marques, Igor; Gomes, José R. B.; Thomas, Jim A.; Félix, Vítor
Abstract: The interaction of the self‐assembled trinuclear ruthenium bowl 1 3+, that displays three other accessible oxidation states, with oxo‐anions is investigated. Using a combination of NMR and electrochemical experimental data, estimates of the binding affinities of 1 4+, 1 5+, and 1 6+ for both halide and oxo‐anions were derived. This analysis revealed that, across the range of oxidation states of the host, both high anion binding affinities (>10 9   M −1 for specific guests bound to 1 6+ ) and high selectivities (a range of >10 7   M −1 ) were observed. As the crystal structure of binding of the hexafluorophosphate anion revealed that the host has two potential binding sites (named the α and β pockets), the host‐guest properties of both putative binding sites of the bowl, in all of its four oxidation states, were investigated through detailed quantum‐based computational studies. These studies revealed that, due to the interplay of ion‐ion interactions, charge‐assisted hydrogen‐bonding and anion‐π interactions, binding to the α pocket is generally preferred, except for the case of the relatively large and lipophilic hexafluorophosphate anionic guest and the host in the highest oxidation states, where the β pocket becomes relatively favourable. This analysis confirms that host‐guest interactions involving structurally complex supramolecular architectures are driven by a combination of non‐covalent interactions and, even in the case of charged binding pairs, simple ion‐ion interactions alone cannot accurately define these recognition processes. Abstract : The interaction of a redox‐active trinuclear, self‐assembled Ru metallomacrocycle with oxo‐anions is reported and its affinity for these anions and halides in different oxidation states is calculated, revealing both high affinities (>10 9   M −1 for some guests) and high selectivities (a range of >10 7   M −1 ). Detailed quantum‐based computational studies on the host in each of its oxidation states, revealed that it binds anion guests by a combination of non‐covalent interactions, including charge‐assisted hydrogen bonding and anion‐π interactions.